Openness of Andalusian Society to Female Poetry - benhaffaf, hadda (El Omda in Linguistics and Discourse Analysis, 2025)
The Arab-Andalusian culture left a true priceless heritage in which women had their fair share in writing poetry on various subjects, and nature’s stunning beauty was a helping factor in bringing out their magical thoughts and intellect. Women’s poetry as a way of literary expression was not new in that era, in spite of those who claim that it was restricted to certain subjects, and was not documented and saved as it should have. So we must ask 1- what were the reasons behind the openness of the Andalusian society to women’s poetry?